A new ligand for copper-catalyzed amination of aryl halides to primary(hetero)aryl amines. Issue 13 (26th March 2020) - Jiang, Shang; Dong, Xinrui; Qiu, Yatao; Chen, Dong; Wu, Xiaoxing; Jiang, Sheng
Graphical abstract: Highlights: An efficient method to prepare primary (hetero)aryl amines was developed. Ligand 2 was found to be a novel efficient ligand for copper-catalyzed amination. This method used cheap aqueous ammonia as the amino source. This method was proceeded under mild conditions with broad substrate scope. Abstract: N, N ′-Bis(3, 5-dimethoxyphenyl)cyclopentane-1, 1-dicarboxamide was found as a new ligand for copper-catalyzed amination of aryl iodides, bromides and chlorides to afford various primary (hetero)aryl amines. These reactions proceeded efficiently under mild conditions when inexpensive aqueous ammonia (28% NH3 in H2 O) was used as the amino source.